Problem leksykalnej relacji filiacyjnej między biblijnymi przekładami renesansowymi. Casus Nowego Testamentu Biblii Jakuba Wujka (1599) i Nowego Testamentu Biblii brzeskiej (1563) - Lisowski, Tomasz (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2015)
The purpose of the analysis is to try to provide an answer to the question whether it is possible to determine the degree of filiational dependence of the New Testament of the Bible translated by Jakub Wujek from 1599 (abbreviation: W) from the New Testament of the Brześć Bible from 1563 (abbreviation: B) with regard to lexis. The study is accompanied by the assumption that the translation of the Brześć Bible may have partially inspired Jakub Wujek in his translation work. The data which enabled scholars to establish the scope of a possible filiational relation between the New Testament of the Bible by Wujek and the New Testament of the Brześć Bible with reference to lexis have been obtained owing to a quantitative-distributional analysis of both texts. Moreover, a comparative context has been considered, that is that between the New Testament of Gdańsk (1606) and the New Testament of the Gdańsk Bible (1632) as texts remaining in closer filiational relation with B, forming a Calvinist-Lutheran translational continuum with this translation. During the study, the number of identical lexical substitutions in place of parallel lexemes common for B and W were treated as an exponent of the degree of hypothetical lexical dependence of W from B. In the subsequent translations of the comparative context under consideration (W and B) they were replaced by alternative equivalents. The result of the analysis with the criteria thus defined is the contention that lexical dependence of W from B is hardly noticeable, which can be proved by the following numerical data: W contains 65 lexemes in total which evidence the studied dependence (they belong to the vocabulary with a frequency f = 1, exceptionally f = 2 or f = 3). They constitute barely 1.2% of the entire lexicon of W, and their total number of occurrences in the text amounts to 74, which is only 0.06% of the entire text of W.